Analysis of Patient Satisfaction Levels on the Quality of Pharmaceutical Services at the Pharmacy Installation of the Batam City Regional General Hospital - Azlina Anwar; Suhatri; Delladari Mayefis; Nahrul Hasan; Malik (Formosa Journal of Science and Technology, 2023)
This study aims to determine the level of patient satisfaction with the quality of pharmaceutical services in the pharmaceutical installation at the Batam City Regional General Hospital. This study uses 5 dimensions of quality (servqual) namely the dimensions of reliability, responsiveness, assurance, empathy, and tangibles. This research is included in the non-experimental type and cross-sectional approach using simple random sampling method. Data analysis was carried out descriptively by comparing the perceived value and expectation value and then connected with the range value to get the patient satisfaction level. The results of the study showed that the level of patient satisfaction had a significant effect on the quality of pharmaceutical services (p<0.05). The highest level of patient satisfaction was found on the tangible dimension of 0.94, and the lowest patient satisfaction was found on the responsiveness dimension of 0.83. This can be interpreted that the level of patient satisfaction is high with pharmaceutical services at the Pharmacy Installation of the Batam City Regional General Hospital.